The Influence of Leadership Style on Employee Performance at the Gowa Regional SAMSAT Office - Novia Ramadhani; Muchriady Muchran; Syahidah Rahmah (GoodWill, 2026)
This study examines the influence of leadership style on employee performance in a public service organization, emphasizing the mediating role of work motivation and organizational commitment. Using a quantitative approach, data were collected from 150 employees through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The findings reveal that transformational leadership has a positive and significant effect on employee performance, both directly and indirectly through work motivation. Transactional leadership also shows a significant but weaker effect, while laissez-faire leadership demonstrates no meaningful contribution. Furthermore, work motivation and organizational commitment are found to significantly mediate the relationship between leadership style and performance outcomes. These results suggest that leaders who inspire, communicate clear visions, and support employee development can enhance productivity and organizational effectiveness. The study contributes to the existing literature by integrating multiple leadership dimensions within a single analytical framework and providing empirical evidence from a developing country context. Practical implications highlight the importance of leadership training programs focused on transformational behaviors to strengthen employee engagement and performance. Future research is recommended to incorporate longitudinal designs and broader sectoral samples to improve generalizability. Overall, this research underscores the strategic role of leadership in fostering high-performing organizations in dynamic institutional environments. Additionally, policy makers should align human resource strategies with leadership development to ensure sustainable performance improvements across public sector institutions.